TRIASTHLET (Three Eyes of Athlete Welfare): Upaya Perlindungan Hukum dan Hak Atas Kesejahteraan Atlet Sepak Bola pada Masa Pandemi Covid-19 di Indonesia - Herlin Sri Wahyuni; Irqi Sheva Maulana; Luna Dezeana Ticoalu (Jurnal Hukum Lex Generalis, 2021)
Soccer athletes currently have a condition that is exacerbated by the Covid-19 pandemic. One of them is related to the current work contract of soccer athletes and also how to resolve disputes related to the problem. Therefore, the authors make an alternative solution to the problem, namely "TRIASTHLET (Three Eyes of Athlete Welfare): Legal Protection Efforts and Rights to the Welfare of Football Athletes During the Covid-19 Pandemic in Indonesia" which is in the form of a concept of protection, fulfillment of athlete's rights and dispute settlement athletes who litigate. The research method used is juridical normative with a statutory approach and a conceptual approach.